Body mass index, weight change, and risk of second primary breast cancer in the WECARE study: influence of estrogen receptor status of the first breast cancer. (3rd October 2016) - Brooks, Jennifer D.; John, Esther M.; Mellemkjær, Lene; Lynch, Charles F.; Knight, Julia A.; Malone, Kathleen E.; Reiner, Anne S.; Bernstein, Leslie; Liang, Xiaolin; Shore, Roy E.; Stovall, Marilyn; ,; et al.
Abstract: Studies examining the relationship between body mass index (BMI) and risk of contralateral breast cancer (CBC) have reported mixed findings. We previously showed that obese postmenopausal women with estrogen receptor (ER)‐negative breast cancer have a fivefold higher risk of CBC compared with normal weight women. In the current analysis, we reexamined this relationship in the expanded Women's Environmental Cancer and Radiation Epidemiology (WECARE) Study, focusing on the impact of menopausal status and ER status of the first breast cancer. The WECARE Study is a population‐based case–control study of young women with CBC (cases, N = 1386) and with unilateral breast cancer (controls, N = 2045). Rate ratios (RR) and 95% confidence intervals (CI) were calculated to assess the relationship between BMI and risk of CBC stratified by menopausal and ER status. Positive associations with obesity and weight gain were limited to women who became postmenopausal following their first primary breast cancer. Among those with an ER‐negative first breast cancer, obesity (vs. normal weight) at first diagnosis was associated with an increased risk of CBC (RR = 1.9, 95% CI: 1.02, 3.4). Also, weight gain of ≥10 kg after first diagnosis was associated with an almost twofold increased risk of CBC (RR = 1.9, 95% CI: 0.99, 3.8). These results suggest that women with an ER‐negative first primary cancer who are obese at first primary diagnosis or who experience a large weight gain afterward may benefit from heightened surveillance. Future studies are needed to address the impact of weight loss interventions on risk of CBC. Abstract : This large case–control study examined the relationship between body mass index at first diagnosis and weight gain following first diagnosis and risk of contralateral breast cancer (CBC). The results suggest that obese women may benefit from heightened surveillance following an estrogen receptor‐negative breast cancer diagnosis. Future studies are needed to address the impact of weight loss interventions on risk of CBC.